Cavalcade of Champions - Unknown (Tufts Archival Research Center, 2008)
19 x 15. Drawing featuring Tufts athletes: Nevin Sayre, Heather Sibbison, Mike Krueger, Lisa Raffin, David Piermarini, James Wong, Lisa Stern, Nancy Stern, Troy Cooper.